Front matter Ecologies of Change (The Strategic Review for Southern Africa, 2020)
Ecological and agricultural change, technological changes, economic policy, gender transitions and the dynamics of a developmental state including accountable intelligence services, people-oriented foreign policy implementation are among subjects that are in this journal edition. These are subjects that have long been in mega discussions about strategic political dynamics of southern Africa and Africa. They are about thinking afresh on questions that have a bearing on the lives of the 450 million people of the region. These are discussions that focus us on the age-old pursuit of a state that responds to human needs. These issues cannot be addressed without research that seeks to clarify what these needs are and what this desired state might be, research that reflects on what work has been done in these directions. In this edition, the authors also thus contribute to the much-needed expansion of what strategic studies in Africa would entail, that it would imply much more than an outgrowth of military or war studies as it unfortunately has been in Eurocentrism. The expanded purview of strategic studies concerns us with human interests, social welfare, environmental justice and technological innovation for human good as much as it focuses on questions of hard power, security and the state.